Alimentação escolar e agricultura familiar: uma análise sobre a implementação da Lei 11.947/2009 e seu caráter sustentável no Sudoeste do Paraná - Gregolin, Graciela Caroline (2016)
This study had the main objective investigate the participation of family farming in the National School Meal Program NSMP, in Paraná Southwestern, at the local's schools, during the year 2013, considering that the Law 11.947/2009 requires that 30% of money transferred by the National Fund for Education Development - NFED to municipalities, states and the Capital, have to be invested in foodstuffs of family farming, promoting food and nutrition security, and - in this way - the sustainable development. First of all, it was carried out a literature research, which showed the relationship between development, sustainability and food, emphasizing the importance of the National Food Program. About the methodology, it was a case study with an exploratory view, and a quantitative and qualitative character, divided into two stages. In the first stage, there was a large research about the NSMP in the municipalities of Paraná Southwest; having noticed that, from the 42 municipalities in the Southwest, only 24 (57%) actually participated. At that time, the investigated was the Technical Manager of Nutrition (TMN) by the municipal school feeding. Posteriorly, after discovering who was the municipality with the highest percentage of purchases of family farming (Francisco Beltrão), and a municipality with acquisition of less than 30% (Pato Branco); the studied went ahead to the second stage of the research, interviewing all the stakeholders related to the NSMP, trying to identify the strengths and weaknesses of each municipality. Thus, it was found that 13 municipalities of the Paraná Southwest reached the percentage of acquisition in 2013, while 11 municipalities have not reached the required amount. Therefore, the most obvious difficulties in Paraná Southwest are: little diversity, quality and quantity of products, low number of family farmers within the program, and insufficient technical assistance. Despite the relevance of public policy studied, as to a healthy eating as to promote sustainable development, implementation of PNAE - unfortunately - it has not been effective. Finally, about the cities Pato Branco and Francisco Beltrão, it was observed that the support from the Government, the organization of family farming, the diversification of food along with agribusiness, may be determining factors in the implementation of these public policy